2006
DOI: 10.1038/sj.onc.1209448
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of the novel BRAFV599Ins mutation detected in a classic papillary thyroid carcinoma

Abstract: Activating mutations of the BRAF gene are the most common genetic alterations in papillary thyroid carcinomas (PTCs) and the T1799A transversion, resulting in BRAF V600E , appeared virtually unique in this cancer type. Here, we report on the identification in a classic PTC of a novel BRAF mutation, namely a 1795GTT insertion, resulting in BRAF V599Ins , and describe its biochemical and molecular characterization. Kinase assays carried out on BRAF V599Ins and BRAF V600E revealed a three-to five-fold increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
1
39
0
2
Order By: Relevance
“…5 A few other BRAF mutations were also observed in PTC, including BRAF K601E (formerly named BRAF K600E ) and BRAF 599ins mutations, and their oncogenic function were welldocumented. 6,7 By direct genomic DNA sequencing, we identified two cases of PTC samples from a BRAF mutation study published previously, 8 whose DNA sequencing chromatogram showed an overlapping pattern of nucleotide sequence starting at base position T1799 in the BRAF gene (Fig. 1).…”
mentioning
confidence: 99%
“…5 A few other BRAF mutations were also observed in PTC, including BRAF K601E (formerly named BRAF K600E ) and BRAF 599ins mutations, and their oncogenic function were welldocumented. 6,7 By direct genomic DNA sequencing, we identified two cases of PTC samples from a BRAF mutation study published previously, 8 whose DNA sequencing chromatogram showed an overlapping pattern of nucleotide sequence starting at base position T1799 in the BRAF gene (Fig. 1).…”
mentioning
confidence: 99%
“…In total, mutations that result in a V600E substitution in BRAF and consequent constitutive activation occur in approximately 45% of PTCs in adults, making BRAF mutations the most common defined genetic abnormality in thyroid cancers (Xing, 2005). In addition to the V600E mutation, rare thyroid tumours have been described with mutations at the 599 and 601 locations that also result in constitutive activation of BRAF kinase Moretti et al, 2006E). It has recently been recognised that rearrangements involving BRAF and AKAP9 that result in increased BRAF signalling occur in a small subset of PTCs .…”
Section: Braf Mutations In Ptc Tumorigenesismentioning
confidence: 99%
“…Less frequent BRAF mutations (5,6) with alterations in the same crucial site, such as Threonine599 and Serine601 (7), have been described. Herein, we report a single case of primary cutaneous melanoma showing a mutation occurring in the P-loop activating site (c.1797_1798insACA, T599insT), which was not previously described in melanomas, but only rarely found in Pilocytic Astrocytoma (PA), Papillary Thyroid Carcinoma (PTC) and Anaplastic Thyroid Carcinoma (ATC) (8)(9)(10)(11). In silico and in vitro data indicate that rare and/or complex mutations in codons 599-601 increase kinase activity similarly to the typical V600E (8,9,12,13).…”
Section: Introductionmentioning
confidence: 86%
“…Genetic analysis showed a rare aminoacidic insertion in codon 599 of the BRAF gene (1797_1798insACA, T599insT: Although in this study and in cited reports (8,(10)(11)(12)(13)(14) all mutations lead to the same T599dup alteration at amino acid level, at DNA level they are described as an ACA duplication (11,12), and as an insertion of TAC between C and A in the other studies. In silico analysis, performed on BRAFV599ins and BRAFT599insT (9,12), indicates that mutations involving the P-loop make the active geometrical conformation more stable than the wild-type counterpart, causing an highly productive catalytic state. In vitro kinase assays carried out on BRAFV599ins and BRAFV600E (9) revealed a three-to-five-fold increase in the enzymatic activity (BRAF-induced phosphorylation of MEK and MAPK) of both mutants compared to BRAFWT.…”
Section: Case Reportmentioning
confidence: 99%